Exploration of Factors Associated With Reading Strategy, Reading Anxiety and Reading Comprehension Ability among English Foreign Language Learners - Azis, Musdizal; Wilymafidini, Okti (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2024)
Based on empirical evidence, a significant portion of students encounter challenges in their reading skills. Specifically, many struggle with low reading comprehension, possess a limited vocabulary, and lack effective reading strategies. Moreover, students often experience anxiety while reading due to difficulties in grasping vocabulary and comprehending textual elements. In contrast, this study delved into the reading strategies and reading anxiety of EFL learners concerning their reading comprehension ability. Employing a correlational study design, the research revealed a correlation coefficient (R) of 0.418, indicating a moderate correlation between the independent variables (reading strategy and reading anxiety) and reading comprehension ability. Thus, it can be inferred that there exists a moderate correlation between students' reading strategies, reading anxiety, and their reading comprehension ability.